Um estudo antropológico das práticas pedagógicas desenvolvidas no seminário integrado na instituição de ensino Edna May Cardoso - Luquini, Jerfferson Paim (2016)
This research, carried out with the post-graduate program in Social Sciences of the Federal University of Santa Maria (UFSM) in the line of research called Social Identities, Ethnicity and Education, investigated the pedagogical practices developed in the discipline of integrated seminar, leading In consideration of the (im) possibilities of an interdisciplinary practice in the area of Human Sciences. In order to develop this research, I set out to answer the following research problem: Considering the Pedagogical Proposal for Polytechnic Secondary Education and Integrated Professional Education for Higher Education 2011-2014, how are the pedagogical practices developed within the framework of the integrated seminar taking place? Into account the dialogue between Philosophy, Sociology, History and Geography? For that, the investigative course was: Ethnographic work carried out at the Edna May Cardoso School, located in the eastern part of the city of Santa Maria-RS, in addition to in-depth interviews with teachers. The data reveal how challenging the restructuring proposal of High School is, as well as shows the difficulties of teachers in creating an interdisciplinary dialogue within the discipline of integrated seminar. Thus, in view of the whole scenario found, we conclude that the dialogue between the disciplines does not occur for a number of factors, such as: working hours in more than one school, single teachers planning and conducting activities related to the discipline of Seminar, and the system is still structured in a disciplinary way. This last factor brings with it a particularity, since breaking with this disciplinary tradition, and from then on starting to work in an interdisciplinary way has been one of the issues facing the integrated seminar and the teachers. Finally, it was identified, described and problematized the pedagogical practices found, mapping the possibilities and impossibilities of an interdisciplinary practice that emerged from it, seeking at all times to make a dialogue in the interface between the Anthropology and the Sociology of Education.